Evaluation of fungicides as protective and curative treatments against canker disease of eucalyptus urograndis caused by chrysoporthe deuterocubensis in Malaysia - Ambrose, Annya; Peter Remun, Attlee Banyang; Shamsul Kamar, Nura Adilla; Mohamad Pazi, Ahmad Mustapha; Wan Azhar, Wan Muhammad Azrul; Awing, Norida Hanim; Liam, Jack; Terhem, Razak (Multidisciplinary Digital Publishing Institute, 2023)
Over the years, Eucalyptus plantations have rapidly expanded in Sarawak, Malaysia, accounting for 19% of the total forest plantation area. In a routine forest health surveillance conducted in 2022 at Sarawak, Malaysia, tree stands of Eucalyptus urograndis (Eucalyptus grandis × Eucalyptus urophylla hybrid) were detected with symptoms of stem canker disease caused by Chrysoporthe infection. Given the limited information on the chemical control of Chrysoporthe stem canker disease, there is a growing need to develop effective chemical control strategies to protect and cure Chrysoporthe infection on E. urograndis trees. Therefore, this study aimed to identify the causal pathogen of this stem canker disease in 7-year-old E. urograndis trees in Sarawak, Malaysia, and evaluate the efficacy of various fungicides as curative or protectant treatments on canker infection using artificial inoculation methods. Fungal isolates were first collected and subjected to molecular identification and pathogenicity analysis. Then, in vitro efficacy tests were evaluated using five licensed fungicides: thiram, prochloraz manganese chloride, copper hydroxide, dimethomorph, and mancozeb. Subsequently, the performance of these fungicides was assessed through preventive and curative field experiments on 10-year-old E. urograndis trees using the artificial inoculation technique. Based on the morphological and phylogenetic analysis of the ITS1/ITS4, β-tubulin 2 (BT2), and the combined ITS1/ITS4 and BT2 sequences extracted from 20 fungal isolates, Chrysoporthe deuterocubensis was identified as the causal pathogen of the canker disease, with isolate CHRY18 recording the highest virulence. The in vitro efficacy tests showed that prochloraz manganese chloride achieved 100% inhibition against C. deuterocubensis at 1.0 mg/mL. In the preventive experiment, thiram significantly inhibited C. deuterocubensis infection, yielding the shortest lesion length (19.40 mm) compared to the non-treated control (47.48 mm) at 20 weeks post-inoculation. In the curative experiment, a significant reduction of 54.7% in lesion length was observed in inoculated symptomatic trees after 20 weeks of post-fungicide treatment with copper hydroxide. In conclusion, this study demonstrated prochloraz manganese chloride, thiram, and copper hydroxide as effective chemical controls of C. deuterocubensis stem canker on E. urograndis.